Identification of Insect Pests Affecting Hydroponic Lettuce in the Experimental Garden at the Faculty of Agriculture, University of Muhammadiyah Palembang - Ika Paridawati; Dessy Tri Astuti; Oktaria Oktaria (Journal of Global Sustainable Agriculture, 2026)
Lettuce (Lactuca sativa L.) is a horticultural commodity widely cultivated using hydroponics due to its economic value and relatively short harvest cycle. However, hydroponic lettuce remains susceptible to insect pest infestations that can reduce both yield quality and quantity. Information regarding the types of pests, infestation levels, and damage symptoms affecting hydroponic lettuce at the Experimental Garden of the Faculty of Agriculture, Universitas Muhammadiyah Palembang, remains limited; thus, field data is required to inform pest management strategies. This study aimed to identify insect pests and determine their infestation levels on hydroponic lettuce plants at the Experimental Garden of the Faculty of Agriculture, Universitas Muhammadiyah Palembang. The research was conducted between October and December 2025 using a survey method with purposive sampling. The study sample consisted of two lettuce plants monitored over four observation sessions. Direct observations were made to detect the presence of pests and symptoms of plant damage. Collected insects were identified based on morphological characteristics using taxonomic keys. Infestation levels were calculated using the formula: IS = (number of infested plants / total number of observed plants) × 100%. The results revealed the presence of aphids (Aphis sp.) and red spider mites (Tetranychus urticae). Aphids were the dominant pest, with an infestation level of 50%, while T. urticae showed an infestation level of 25%. Observed symptoms included leaf yellowing and stunted growth. The findings indicate that pest presence is associated with environmental conditions and crop sanitation. These data can serve as a basis for implementing integrated pest management in hydroponic lettuce cultivation.